Performance of Thermal Power Plants in Tropical, Dry, Temperate, Continental, and Polar Climate Regions - Rabah, Ali; Mohamed Omer Sidahmed; Asaad Y. Shamseldin (University of Khartoum Engineering Journal, 2025)
The current body of literature lacks information about the impact of geographical location, particularly climatic regions, on thermal power plant performance. This study aimed to bridge this gap by investigating how different climatic conditions impact the performance of thermal power plants. As a case study, it considers a 100 MW thermal power plant operating on the ideal Rankine cycle with superheat and reheat principles. Climate data spanning 30 years (1991-2021) is collected for 92 locations across various climatic regions: tropical, dry, temperate, continental, and polar regions. The Engineering Equation Solver (EES) of F-Chart Software is used to integrate energy and climate data to facilitate analysis of thermal power plant performance. The findings reveal that, on average, the ambient temperature in tropical climate exceeds that of dry, temperate, continental, and polar climates by 4°C, 10°C, 17°C, and 26°C, respectively. In comparison to other climatic regions, thermal power plant located in tropical and dry climates exhibit lower efficiency (1.0 to 3.0), higher makeup water requirement (12.0 to 30.0), increased cooling water demand (5.0 to 11.0), and elevated fuel consumption and CO emissions (3.0 to 6.5). The study confirms that continued reliance on thermal power plants in dry and tropical climates lack reliability and sustainability. Transitioning towards abundant renewable energy sources in these regions helps in reducing fossil oil depletion and mitigating CO emissions. In addition, it enhances the resilience and sustainability of energy infrastructure, particularly in regions vulnerable to water scarcity.